(untitled) (Journal of Medicine, 2015)
A 52 year old female reported to surgery department of Bangabandhu Sheikh Mujib Medical University (BSMMU) with dysphasia and exertional chest pain. With detailed history and examination she was diagnosed as a case of epigastric mass and undergone X-ray chest. The report revealed enlarged mediastinal shadow with suspicion of thoracic aortic aneurysm. X-ray chest was followed by contrast enhanced CT scan which revealed a large partially thrombosed aneurysmal dilatation of the aortic arch with sharp kinking (bend) at distal end of aneurysm and beginning of descending aorta. Then the patient was referred to cardiac surgery for immediate management. But the patient refused to have a surgery. Then two months later the patient again presented with chest pain and admitted in DMCH. But the patient died. DOI: http://dx.doi.org/10.3329/jom.v16i1.22405 J MEDICINE 2015; 16 : 53-55